Vivencias y emociones familiares en confrontación: el grupo como contexto constructivo de una ecología de ideas innovadoras en torno al estado de seropositividad del hijo - Aguayo, José (2000)
The authors propose a ten group sessions experience with four mothers assisting their sons and daughters infected with AIDS. The aim was to co-create a conversational context where suffering and isolation were replaced  a new attitude. So, the themselves become a sane perturbing element at their own family system level. There is described the methodology used in this research-action experience, even regarding group conduction aspects.